1986
DOI: 10.1152/ajpendo.1986.250.2.e169
|View full text |Cite
|
Sign up to set email alerts
|

Regional ketone body utilization by rat brain in starvation and diabetes

Abstract: The rate of ketone body (beta-hydroxybutyrate and acetoacetate) metabolism was measured in individual cerebral structures of fed, starved, and diabetic rats. This was done by infusing beta-[3-14C]hydroxybutyrate intravenously and measuring the incorporation of 14C into brain by quantitative autoradiography. The capacity of the brain to use ketone bodies, expressed as plasma clearance, increased in starvation and diabetes by approximately 50-60%. Plasma clearance was near maximal after 2 days starvation and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 5 publications
9
90
0
Order By: Relevance
“…Because total glucose utilization was not measured in the present study, we cannot say whether the reduction in V pdhN with increasing V AcCoA-kbN corresponded to reduced or unchanged glucose utilization (e.g., net lactate formation followed by efflux). Reduced brain glucose utilization and increased lactate efflux is seen during prolonged fasting-induced hyperketonemia in humans 32 and rats, 27 suggesting that a larger glycolytic component than we estimate based on pyruvate oxidation during maximum ketone use, cannot be fully excluded.…”
Section: Implications Of Ketone Body Oxidation For Models Of Neuroenementioning
confidence: 80%
“…Because total glucose utilization was not measured in the present study, we cannot say whether the reduction in V pdhN with increasing V AcCoA-kbN corresponded to reduced or unchanged glucose utilization (e.g., net lactate formation followed by efflux). Reduced brain glucose utilization and increased lactate efflux is seen during prolonged fasting-induced hyperketonemia in humans 32 and rats, 27 suggesting that a larger glycolytic component than we estimate based on pyruvate oxidation during maximum ketone use, cannot be fully excluded.…”
Section: Implications Of Ketone Body Oxidation For Models Of Neuroenementioning
confidence: 80%
“…25 It has been shown that the STZ-treated rats had globally increased CMR glu and cerebral ketone utilization at 1 week. 25,39 The regional CMR glu in almost all the brain regions recovered to normal level at 4 weeks, but this is accompanied by further increased contribution of ketone bodies to brain energy metabolism 25,39 and reduced regional cerebral blood flow in selected brain regions including the striatum. 29 It thus appears that, in response to the evolving consequences of sustained hyperglycemia, the diabetic brain must be in a constant process of adaption trying to reach a new homeostasis state for energy metabolism, and it may make use of alternative substrates such as Glu, in a region-specific manner, 39 under circumstances when these substrates are needed and available.…”
Section: Glutamate Reduction After Insulin Injectionmentioning
confidence: 99%
“…It has been proposed by Cahill (1982) that ketone metabolism may not be important in animals with lower brain/body ratios. Extending this hypothesis further, Hawkins et al (1986) posed an interesting notion that 'whether a requirement for the expansion of the cerebral cortex during the course of human evolution was the improved ability to use ketone bodies during time of need'.…”
Section: Species Differencesmentioning
confidence: 99%